PARALLEL ANALYSIS OF PHYSICAL ACTIVITY AND SEDENTARY TIME SPENDING OF FEMALE STUDENTS OF LOWER ELEMENTARY TEACHING AT FACULTY OF PHILOSOPHY IN RELATION TO PRESENT PHYSICAL AND MENTAL FATIGUE AND ART OF USING THE VALUE CONTENT OF PERSONAL PHYSICAL EDUCATION - Grujo Bjeković; Nenad Lalić; Đorđe Arnaut (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Classifying female students of Faculty of Philosophy Department of Lower Elementary Teaching (85) has been carried out according to evidences of the physical activity questionnaire and sedentary time spending, classifying female students into separated taxonomic groups by use of hierarchy of cluster analysis. By method of multiple analysis of variance it has been established the statistical importance of classifying female students into typical groups appropriate for parallel analysis of their characteristics in relation to: present physical and mental fatigue and knowledge, and art of using the value contents of personal physical education in accordance with the scope of physical activities and sedentary time spending in day regime. Individual profiles of the surveyed evidences have been adduced according to the typical groups for the purpose of case study of the ratio of female students to the value contents of personal physical education. The purpose of that kind of monitoring is recognition of needs for creation and implementation of the peculiar contents, methodology and forms of personal physical education appropriate for creative physical/bodily and practical spiritual accomplishment of female students by the culture of motion activity. The personal culture of motion activity of female students is apprehended as basic prerequisite for their complete development and self-accomplishment by peculiar ratio to all aspects of personal culture of personality.